Direct Conversion of Dry Algae to Biodiesel under Supercritical Methanolysis: An Advanced Research - Hawash, S.; El- Enin, S. A. Abo; Diwani, G. El (New Innovations in Chemistry and Biochemistry Vol. 3, 2021)
The study aims to conversion of dry algal biomass into biodiesel in a one-step process under supercritical methanol conditions for an environmentally friendly approach and economical. At supercritical conditions, methanol is used to extract and transesterify lipids from algae, resulting in fatty acid methyl esters. The process conditions inhibited the formation of byproducts, and the fatty acid methyl esters are made from polar phospholipids, free fatty acids, and triglycerides. The effects of dry algae to methanol (weight/volume) ratio (1:12-1:40), reaction temperature (150-300°C), and reaction time (5–50 min.) on the yield of fatty acid methyl esters are investigated. At 300°C, with a molar ratio of 1:30 (weight/volume) and a reaction period of 30 minutes, the conversion percentage reached 97 percent. Gas chromatography analysis was used to determine the purity of fatty acid methyl ester, which was found to be 80 percent pure and the alkyl ester content to be 77.6%. This green conversion method has the potential to provide an energy-efficient and economical route for biodiesel production, with a high predicted cetane number (60), high oxidation resistance, and low viscosity.